2019
DOI: 10.2320/jinstmet.j2018046
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Behavior of Wrought Fe-Ni-Based Alloy HR6W

Abstract: Age hardening behavior of Fe Ni based alloy HR6W was investigated at the temperature range between 973 K and 1073 K. Two step increase in hardness is detected for the alloy at each temperature; the rst increase in hardness results from the precipitation of M 23 C 6 phase and the second one corresponds to that of Laves phase. The TTP time temperature precipitation diagram for the alloy is established based on the results of hardness measurement and microstructure observation, where the precipitation of Laves ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In recent years, heatresistant steels that utilize Laves phases as strengthening particles have been developed, and it has been reported that these steels have both superior high-temperature strength and good ductility compared with conventional steels. [20][21][22][23][24][25] Takeyama 25) reported that creep strength can be enhanced without loss of ductility by densely surrounding the grain boundaries with the Fe 2 Nb Laves phase. Thus, unified knowledge on the effect of the Laves phase in heat-resistant steels on the ductility and toughness of steels is required.…”
Section: Evaluation Of Cleavage Fracture Behavior Of C14 Fe 2 W Laves...mentioning
confidence: 99%
“…In recent years, heatresistant steels that utilize Laves phases as strengthening particles have been developed, and it has been reported that these steels have both superior high-temperature strength and good ductility compared with conventional steels. [20][21][22][23][24][25] Takeyama 25) reported that creep strength can be enhanced without loss of ductility by densely surrounding the grain boundaries with the Fe 2 Nb Laves phase. Thus, unified knowledge on the effect of the Laves phase in heat-resistant steels on the ductility and toughness of steels is required.…”
Section: Evaluation Of Cleavage Fracture Behavior Of C14 Fe 2 W Laves...mentioning
confidence: 99%